2002
DOI: 10.1001/archinte.162.16.1849
|View full text |Cite
|
Sign up to set email alerts
|

Community-Acquired Pneumonia Due to Gram-Negative Bacteria and Pseudomonas aeruginosa

Abstract: Background: Initial empirical antimicrobial treatment of patients with community-acquired pneumonia (CAP) is based on expected microbial patterns. We determined the incidence of, prognosis of, and risk factors for CAP due to gram-negative bacteria (GNB), including Pseudomonas aeruginosa. Methods: Consecutive patients with CAP hospitalized in our 1000-bed tertiary care university teaching hospital were studied prospectively. Independent risk factors for CAP due to GNB and for death were identified by means of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
272
4
26

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 369 publications
(315 citation statements)
references
References 37 publications
(44 reference statements)
13
272
4
26
Order By: Relevance
“…In our study, 29.9 of patients with disease progression after initial antibiotic therapy had received appropriate therapy, and 5 of 10 non-survivors with MDR pathogen infection had received appropriate therapy. Similar studies have also been reported 35,36 , and these ndings suggest that treatment strategies for HCAP other than antibiotic selection are also required. HCAP patients are often functionally disabled, and patient-related factors including functional status may be needed in the analysis of prognostic factors, which was dif cult in the present study due to its retrospective nature.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, 29.9 of patients with disease progression after initial antibiotic therapy had received appropriate therapy, and 5 of 10 non-survivors with MDR pathogen infection had received appropriate therapy. Similar studies have also been reported 35,36 , and these ndings suggest that treatment strategies for HCAP other than antibiotic selection are also required. HCAP patients are often functionally disabled, and patient-related factors including functional status may be needed in the analysis of prognostic factors, which was dif cult in the present study due to its retrospective nature.…”
Section: Discussionsupporting
confidence: 81%
“…34 It is also interesting that the observed mortality for COP was lower than that observed more than 10 years ago despite the high rate of bacteremia, suggesting that these may have been less virulent strains of gram-negative bacteria. 35 The high rates of MDR and IIAT in Pa-NP for all pneumonia types mandate that clinicians have therapeutic strategies in place to optimize therapy. Scoring systems to identify patients with MDR infections, including MDR P. aeruginosa, are available but limited in their overall ability to predict MDR infection.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis (CF) is an autosomal recessive genetic disease (6); the opportunistic pathogen Pseudomonas aeruginosa may cause chronic lung disease in CF patients, depending on the genetic adaptation of the pathogen, and is a prevalent pathogen in CF patients with pulmonary infection (1)(2)(3)(4)(5). Worldwide, 80% of CF patients were found to be infected with P. aeruginosa (7,8).…”
Section: Introductionmentioning
confidence: 99%